2013
DOI: 10.3892/mmr.2013.1387
|View full text |Cite
|
Sign up to set email alerts
|

Expression of basigin in the early phase of acute myocardial ischemia in rats

Abstract: Abstract. Basigin may be involved in cardiovascular disease. In our previous study, suppression subtractive hybridization results indicated that basigin may be associated with the early phase of acute myocardial ischemia (AMI) within 1 h. However, little is known regarding the expression of basigin in the early phase of AMI. The aim of the present study was to evaluate the temporal and spatial expression patterns of basigin mRNA and protein levels in AMI in rats. We constructed an AMI model in rats that receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…10–12 Although some AMI model experiments have attempted to determine the molecular profile alterations associated with short‐term ischemia, elucidation of the acute proteomic changes is challenging if tissues are collected macroscopically. 1314 …”
Section: Introductionmentioning
confidence: 99%
“…10–12 Although some AMI model experiments have attempted to determine the molecular profile alterations associated with short‐term ischemia, elucidation of the acute proteomic changes is challenging if tissues are collected macroscopically. 1314 …”
Section: Introductionmentioning
confidence: 99%
“…2000 ng of total RNA was added to each 40 μl cDNA synthesis reaction, which was reverse transcribed to cDNA using iScript Reverse Transcription Supermix (BioRad). Primer sequences, annealing temperatures and product sizes for quantitative real-time PCR are shown in Table 1 (14,15). Primers were validated by running endpoint PCR with 250 nM forward and reverse primers, 1 μl of cDNA and iTaq Universal SYBR Green Supermix (BioRad) following the manufacturer's instructions.…”
Section: Animals Estrus Staging and Tissue Collectionmentioning
confidence: 99%
“…In yeast and bacteria, 30%-85% of protein levels can be attributed to changes in mRNA expression, the other 15%-70% variation is explained by posttranscription or posttranslation regulation and measurement errors, only 40% of proteins in multicellular organisms can be explained by mRNA (de Sousa Abreu et al, 2009). Studies have shown that more than 70% of the protein expression is regulated by mRNA, in yeast, while only about half of the protein expression in E. coli is regulated by mRNA (Liu et al, 2013;Lu et al, 2007). Besides, we substituted the NQO1 mRNA levels in PBMCs and plasma protein levels for those of brain tissue, which might be possibly different from that in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that more than 70% of the protein expression is regulated by mRNA, in yeast, while only about half of the protein expression in E . coli is regulated by mRNA (Liu et al, 2013 ; Lu et al, 2007 ). Besides, we substituted the NQO1 mRNA levels in PBMCs and plasma protein levels for those of brain tissue, which might be possibly different from that in the brain.…”
Section: Discussionmentioning
confidence: 99%